Understanding Promise: Impact of State Support on Latino High School Student Habitus. Issue 4 (2nd October 2021) - Talan Azizova, Zarrina; Mendez, Jesse Perez
ABSTRACT: This study examined the role of a state need-based financial aid policy in Latina/o high school students' meaning making of postsecondary access. Utilizing narrative research, the analytical focus on the meaning making uncovered patterns of individual agency in the journeys of eight Latina/o high school students who were recent enrollees in the state need-based financial aid program.